Covid Language as a Post-Covid Syndrome – Language Users’ Reactivity to the Reality of the SARS-CoV-2 Pandemic - Wrześniewska-Pietrzak, Marta (Poznańskie Studia Slawistyczne, 2024)
The article contains a review of a book Syndrom postcovidowy w języku. Polsko- -bułgarskie studium przypadku. Raport z badań eksperymentalnych (Postcovid Syndrome in the Language. Polish-Bulgarian Case Study (Experimental Research Report)) written by Natalia Długosz and Andreana Eftimova (2023). The article points out the differences in the research conducted by the authors against the background of publications showing media representations of the coronavirus and the SARS-CoV-2 pandemic, as well as research works presenting the impact of the pandemic on the Polish language. The authors’ proposal is an experimental study in which they try to recreate, on the basis of an experimental study conducted using the survey method, how Polish-speaking and Bulgarian-speaking students recreate specific open definitions of three concepts: corona panic (koronapanika), corona party (koronaparty) and corona tourism (koronaturystyka).